A Systematic Literature Review of Tidal Current Energy in Indonesia - Nurhayati Nurhayati; Pebnaldy Pebnaldy; Hendra Achiari (Syntax Idea)
Tidal energy is considered as one of the most promising forms of renewable energy generation due to its environmental friendliness and predictability. The goal of this work is to conduct a thorough literature review on various approaches for optimizing tidal energy output in Indonesia. Tidal current research published between 2014 and 2022 were chosen for further investigation based on literature criteria. The selected primary papers revealed that contemporary tidal energy research focuses on four subjects and trends: resources, numerical modeling, geographic information systems (GIS), and experimental studies. The findings of this study also indicate methodologies that are commonly mentioned and so important in the field of tidal current energy.